Local governance of the 2014 ebola Epidemic: a PhD synthesis - Sabine Iva Franklin (Global Health Action, 2024)
Background The doctoral dissertation examines how local response efforts were integrated into overall emergency management. Objectives It seeks to understand the role and effectiveness of community-based actors in addressing collective action problems Methods Sixty-seven semi-structured interviews were conducted from January to July 2017 in Liberia and Sierra Leone. Key informants include healthcare workers, traditional leaders, and community stakeholders, such as non-governmental organization representatives and volunteers. Results Findings show that traditional and community leaders responded to the public health emergency via rulemaking, quarantine, travel limitation, healthcare referrals, health sensitization, and door-to-door contact tracing. These actions by local leaders helped to change behaviors and improve cooperation. Sierra Leone had 32.3% more Ebola cases than Liberia but 18% fewer deaths. Sierra Leone had integrated traditional and community leaders before the scale up of international aid resources. Conclusion This suggests that actions taken by traditional and community leaders improved overall efforts, and in some areas, before scaled-up humanitarian interventions. Bilateral engagement with local community actors should be integrated in every public health response to improve cooperation, and it should be done before an intervention is conceived and executed.